The Role of Cyberattacks in Political and Economic Stability: Transforming National and International Approaches - Myrsalieva, Aizhana; Abdrakhmanova, Elia; Suiunduk uulu, Daniyar; Moldomyrzaev , Maksatbek (Law, State and Telecommunications Review, 2026)
[Purpose] The purpose of the study was to identify the main aspects of threats in the cyber sphere to determine recommendations for improving cyber resilience. [Methodology/approach/design] The study used materials from the Centre for Strategic and International Studies (CSIS), reports and publications from Arctic Wolf and UpGuard, cyber resilience indices from MixMode, and publications from the Global Organised Crime Index. The research methods were case studies, statistical analysis, and analysis of official documents. [Findings] The study found that cyber incidents as a phenomenon have been known since at least the early 2000s, but the main increase in activity began after 2015. In addition, the intensity of cybercrime was influenced by international events, such as the 2008 crisis, the coronavirus epidemic in 2020, or the full-scale Russian invasion of Ukraine in 2022. Government structures are among the most common targets of cybercriminals. In this context, cyber warfare, cyber espionage, and hacktivism can be used. It has also been studied that, in the context of the economic consequences of cyber threats, the main target of criminals can be cloud storage, because the volume of data stored in them increases every year. In addition, losses from cybercrimes in 2018 were estimated at 600 billion dollars, and by the mid-2020s they were estimated to have reached approximately 9.2 trillion dollars. The exact number of cyber incidents is extremely difficult to track due to their geographical disparity. In this regard, large companies and corporations are strengthening their cyber resilience, an example of which is the activities of JPMorgan Chase. In the context of individual countries, developed economies are the most resistant to cyber incidents, while in developing countries the situation with cyber resilience is much worse. At the national level, one of the most successful cyber security strategies is the Finnish model. It is also important that the draft resolution “United Nations (UN) Convention against Cybercrime” was approved at the international level. As a result, the international community continues to face threats of cyber incidents, but more and more initiatives are being taken to minimise the risks of cyber threats. [Practical implications] The findings highlight the need for adaptive cybersecurity strategies, particularly in cloud storage protection and national infrastructure. They support the importance of strengthening cyber resilience in developing countries, adopting best practices from successful models (e.g., Finland), and enhancing international coordination. [Originality/value] The study provides a longitudinal analysis of cybercrime trends in relation to major global events, and links the rise in cyber incidents to geopolitical and economic disruptions.